Frailty in heart transplantation: Report from the heart workgroup of a consensus conference on frailty. Issue 2 (29th August 2020) - Kobashigawa, Jon; Shah, Palak; Joseph, Susan; Olymbios, Michael; Bhat, Geetha; Dhital, Kumud; Eisen, Howard; Kransdorf, Evan; Patel, Jignesh; Skorka, Rafael; Pinney, Sean; Wilson, Michael E.; et al.
Abstract : A consensus conference on frailty in solid organ transplantation took place on February 11, 2018, to discuss the latest developments in frailty, adopt a standardized approach to assessment, and generate ideas for future research. The findings and consensus of the Frailty Heart Workgroup (American Society of Transplantation's Thoracic and Critical Care Community of Practice) are presented here. Frailty is defined as a clinically recognizable state of increased vulnerability resulting from aging‐associated decline in reserve and function across multiple physiologic systems such that the ability to cope with every day or acute stressors is compromised. Frailty is increasingly recognized as a distinct biologic entity that can adversely affect outcomes before and after heart transplantation. A greater proportion of patients referred for heart transplantation are older and have more complex comorbidities. However, outcomes data in the pretransplant setting, particularly for younger patients, are limited. Therefore, there is a need to develop objective frailty assessment tools for risk stratification in patients with advanced heart disease. These tools will help to determine appropriate recipient selection for advanced heart disease therapies including heart transplantation and mechanical circulatory support, improve overall outcomes, and help distinguish frailty phenotypes amenable to intervention. Abstract : This article reports the Frailty Heart Workgroup's deliberations regarding standardization of frailty nomenclature and assessment as well as the approach to frailty in heart failure and heart transplant patients.